The Penderwicks a summer tale of four sisters, two rabbits, and a very interesting boy - Birdsall, Jeanne (Yearling, 2005)
While vacationing with their widowed father in the Berkshire Mountains, four young sisters, ages four through twelve, share adventures with a local boy, much to the dismay of his snobbish mother.